Chakras in the Boardroom: Integrating Ancient Wisdom with Modern Business Practices for Enhanced Emotional and Spiritual Intelligence - Ratmayanti, Nyoman Gita Saraswati; Nugroho, Albertus Henri Listyanto; Darmawan, I Made Dwi Hita; Wiratama, Awang Bagas (UIN Sunan Gunung Djati Bandung, 2023)
This study explores the application of chakra philosophy in business management practices. Chakras, defined as energy centers within the human body, are intricately linked with daily human dynamics and spiritual consciousness. The aim of this study is to integrate chakra principles into managerial processes and assess their impact on emotional and spiritual intelligence, performance, accountability, and business sustainability. A qualitative approach was adopted for this study, focusing on four chief executive officers as research subjects. Data collection was conducted using triangulation techniques, including document analysis and semi-structured interviews. The results indicate that the implementation of chakra philosophy by chief executives contributes to the stability of emotional and spiritual intelligence. This, in turn, enhances performance, accountability, and the sustainability of the business. This research contributes a novel perspective by elaborating on the application of chakra philosophy in business management. It offers a new approach to managing and sustaining a company by considering individual management aspects and organizational culture.